Alternatif Konsep Wasaṭiyyah Perspektif Makārim Asy-Syīrāzī: Studi Kitab Tafsīr Al-Amtsal - Ahmed Zaranggi Ar Ridho; Muhammad Iqbal (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2023)
This article attempts to present the concept of wasaṭiyyah in QS. Al-Baqarah [2]: 143 the perspective of ayatollah Makārim Ash-Shīrāzī as an alternative interpretation of anthropocentric religious moderation. The Shiite perspective has always been ignored in the development of the discourse on strengthening religious moderation. Tafsīr Al-Amtsal as a product of the Shi'a Imāmiyyah school of thought which is a minority group in Indonesia is a new offer of the concept of wasaṭiyyah. This research uses descriptive method with content analysis as a data analysis tool by finding three important points of wasaṭiyyah from ayatollah Makārim's perspective. First, the concept of wasaṭiyyah is more inclusive; by referring to the nature and character of moderation, not to certain majority groups of people. Second, the comprehensiveness of the analysis and the breadth of insight into the distinctive contemporary issues. Third, alternative contributions on two aspects: the inclusion of the perspectives of all streams including minorities and prioritizing human moderation before religious moderation. These three points are relevant to the context of plurality and the religious character of Indonesian society and have implications for strengthening Kemenag's religious moderation in terms of meaning and principles that focus onethical-humanist values.